Reliability and validity of the finger flexor dynamometer. (September 2019) - Nestler, Kai; Rohde, Ulrich; Becker, Benjamin; Waldeck, Stephan; Veit, Daniel A; Leyk, Dieter
Introduction: Dynamometric measurement is a low-cost, noninvasive method for diagnosing and evaluating traumatic and degenerative disorders. The purpose of this study was to assess the reliability and validity of a new custom-made finger flexor dynamometer and evaluate the feasibility of the measuring procedure. Methods: Maximum voluntary isometric contraction force at the distal phalanx of the index finger was measured for 1.5 s in 25 healthy volunteers (18–50 yrs). Test–retest reliability and inter-day reliability were assessed by intraclass correlation coefficient model (2, k) on two and five consecutive days, respectively. Both a single measurement and the mean of three repeated measurements were carried out daily. The standard error of measurement was used to measure the absolute reliability, the smallest detectable change was determined, and the coefficient of variation was calculated for each individual. Construct validity was determined by Pearson coefficient. Results: Repeated measurement test–retest reliability was excellent according to Munro's rating scale, with an intraclass correlation coefficient of 0.99 (95%CI: 0.97–0.99), coefficient of variation of 2.6%, and standard error of measurement of 0.4 N. Single measurement test–retest reliability was high to excellent with an intraclass correlation coefficient of 0.94 (95%CI: 0.86–0.97), coefficient of variation of 4.1%, and standard error of measurement of 1.4 N. Smallest detectable change increased from 1.8 N (repeated measurement) to 3.3 N (single measurement). Inter-day reliability intraclass correlation coefficients exceeded 0.93. High construct validity was indicated by a convergent relationship with grip strength (r = 0.85, p < 0.001). Conclusions: The novel dynamometer provides excellent reliability and construct validity and supports an objective diagnosis of finger limitations by quantifying the flexion force magnitude. Traumatic injuries and follow-up of rehabilitative treatment can be monitored more precisely.